ASI Eksklusif Sebagai Faktor Protektif Terhadap Kejadian Stunting Pada Balita 24-59 Bulan - Rafika Surya Putra Pratama; Mohammad Shoim Dasuki; Tri Agustina; Siti Soekiswati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Stunting is a nutritional problem that, until now, has been a concern and an issue that has not been able to be resolved. Exclusive breastfeeding is predicted to minimize the risk of stunting because exclusive breastfeeding contains immune components, antibodies and calcium, and nutrients needed by babies. Objective: To analyze the effect of exclusive breastfeeding on the incidence of stunting in children aged 24-59 months. Method: A literature review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) for data extraction. The databases used include Google Scholar, Science direct, and Pubmed. And Sage Journals using the keywords (“Exclusive Breastfeeding” OR Breastfeeding OR “Breastfed”) AND (Stunting OR “Growth Disorder” OR “Stunted Growth”) AND Toddler. Results: Extraction obtained 16 articles were analyzed. Conclusion: Exclusive breastfeeding for toddlers 24-59 months can be a protective factor against stunting, while non-exclusive breastfeeding can be a risk factor for toddlers experiencing stunting